2018
DOI: 10.1136/bmjopen-2018-023113
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of high-cost patients’ characteristics and healthcare utilisation

Abstract: ObjectivesTo investigate the characteristics and healthcare utilisation of high-cost patients and to compare high-cost patients across payers and countries.DesignSystematic review.Data sourcesPubMed and Embase databases were searched until 30 October 2017.Eligibility criteria and outcomesOur final search was built on three themes: ‘high-cost’, ‘patients’, and ‘cost’ and ‘cost analysis’. We included articles that reported characteristics and utilisation of the top-X% (eg, top-5% and top-10%) patients of costs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
238
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(265 citation statements)
references
References 72 publications
17
238
1
9
Order By: Relevance
“…In our study, it was found that gender, age, education, social welfare status, having a primary caregiver, BMI, dependency level, depression symptoms, IADL functions, mental status, service resources level, and proportion of CNAs significantly affected the HCBS utilization time period based on the regression analysis. These results were mostly consistent with the findings of previous studies [16,17,42,43].…”
Section: Hcbs Utilization Period and Influencing Factorssupporting
confidence: 93%
“…In our study, it was found that gender, age, education, social welfare status, having a primary caregiver, BMI, dependency level, depression symptoms, IADL functions, mental status, service resources level, and proportion of CNAs significantly affected the HCBS utilization time period based on the regression analysis. These results were mostly consistent with the findings of previous studies [16,17,42,43].…”
Section: Hcbs Utilization Period and Influencing Factorssupporting
confidence: 93%
“…To the best of our knowledge, our systematic review and meta-analyses were the first to examine the effects of socioeconomic variation on EOL cost of care. While SES has been shown to be an important determinant of population health across the life continuum [43][44][45][46][47], its relationship with health-care expenditures was less consistent and more variable across jurisdictions [48]. The focus on EOL care has also been less studied than the relationships between SES and health-care during other periods of life.…”
Section: Discussionmentioning
confidence: 99%
“…Such a change has been called for in the literature on ambulatory care sensitive conditions, proper ambulatory care being hypothesised to reduce unplanned acute care. [53] Unplanned acute admissions have been identi ed as a main driver of costs for patients with chronic conditions [54] and are considered a system failure in the delivery of chronic care.…”
Section: Discussionmentioning
confidence: 99%